Modeling The Trade Flows of Leading Fishery Commodities in The Southern Region of Central Java Using The Gravity Model - Ganjar Ndaru Ikhtiagung; Faidzin Firdhaus; Septi Purwaningsih; Sasongko Adi Priyanto (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
While having relatively high fishery production, the southern region of Central Java continues to produce poor and uneven interregional trade flows, reflecting persistent inefficiencies in market integration and spatial connectivity. This quantitative study examines the determinants of interregional trade flows of leading fishery commodities using an extended Gravity Model. Secondary data were obtained from Statistics Indonesia, the Ministry of Marine Affairs and Fisheries, and the Regional Development Planning Agency of Central Java, covering the period of 2018–2024. To explain trade volume between origin and destination regions, the model includes economic mass (Gross Regional Domestic Product), geographical distance, infrastructure quality, interregional price differentials, and market centrality. The findings demonstrate that statistically, the economic size of both the origin and destination regions has a positive and significant effect on trade flows. Distance and price differences, on the other hand, are statistically insignificant, suggesting that spatial separation and short-term price arbitrage are becoming less important. Infrastructure quality shows a positive but insignificant effect, indicating a supportive yet limited role. Meanwhile, market centrality exerts a profound and substantial impact on trade patterns. Theoretically, this study extends the Gravity Model by demonstrating that institutional market concentration outweighs traditional spatial frictions in regional fishery trade.